Play at the center of the curriculum - Van Hoorn, Judith (Boston Pearson, 2011)
"Play at the Center of the Curriculum is a resource for those who want to engage children in a developmental zone where children and teachers are learning. Current and future teachers are guided in methods of supporting children?s progress through play. This book carefully blends theory and practice. As seasoned teachers, we demonstrate how to draw both the methods and the content of a successful curriculum from children?s play. We interweave anecdotes of children?s play, theories of play and development, and instructional strategies that place play at the center of the curriculum."--Publisher's website.
1. Looking at play through teacher's eyes -- 2. Play and development: theory -- 3. Play as the cornerstone of development : the literature -- 4. Orchestrating children's play: setting the stage -- 5. Orchestrating play : interactions with children -- 6. Play as a tool for assessment -- 7. Mathematics in the play-centered curriculum -- 8. Language, literacy and play -- 9. Science in the play-centered curriculum -- 10. The arts in the play-centered curriculum -- 11. Play and socialization -- 12. Outdoor play -- 13. Play, toys, and technology -- 14. Conclusion : integrating play, development and practice.
Keywords: Play; Education, Preschool -- United States; Education, Preschool -- California -- Case studies; Cognition in children